Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the recursive rule for the given geometric sequence [tex]\( f(n) = 13 (1.3)^{n-1} \)[/tex], let's analyze each part of the sequence step-by-step.
1. Initial Term:
The initial term [tex]\( f(1) \)[/tex] is given by plugging in [tex]\( n = 1 \)[/tex] into the formula:
[tex]\[ f(1) = 13 \cdot (1.3)^{1-1} = 13 \cdot (1.3)^0 = 13 \cdot 1 = 13 \][/tex]
So, we have:
[tex]\[ f(1) = 13 \][/tex]
2. Recursive Relationship:
A geometric sequence has a common ratio between consecutive terms. For this sequence, the common ratio [tex]\( r \)[/tex] can be determined from the formula:
[tex]\[ f(n) = 13 \cdot (1.3)^{n-1} \][/tex]
To find the relationship between [tex]\( f(n) \)[/tex] and [tex]\( f(n-1) \)[/tex], consider:
[tex]\[ f(n-1) = 13 \cdot (1.3)^{(n-1)-1} = 13 \cdot (1.3)^{n-2} \][/tex]
To express [tex]\( f(n) \)[/tex] using [tex]\( f(n-1) \)[/tex]:
\begin{align}
f(n) &= 13 \cdot (1.3)^{n-1} \\
&= 13 \cdot (1.3)^{n-2} \cdot (1.3)^1 \\
&= (13 \cdot (1.3)^{n-2}) \cdot 1.3 \\
&= f(n-1) \cdot 1.3
\end{align}
Therefore, the recursive relationship is:
[tex]\[ f(n) = 1.3 \cdot f(n-1) \quad \text{for} \quad n \geq 2 \][/tex]
Combining both the initial term and the recursive relationship, the recursive rule for the geometric sequence is:
[tex]\[ f(1) = 13, \quad f(n) = 1.3 \cdot f(n-1) \quad \text{for} \quad n \geq 2 \][/tex]
Thus, the correct choice is:
\[
f(1)=13, \quad f(n)=1.3 \cdot f(n-1), \quad n\geq 2
\
1. Initial Term:
The initial term [tex]\( f(1) \)[/tex] is given by plugging in [tex]\( n = 1 \)[/tex] into the formula:
[tex]\[ f(1) = 13 \cdot (1.3)^{1-1} = 13 \cdot (1.3)^0 = 13 \cdot 1 = 13 \][/tex]
So, we have:
[tex]\[ f(1) = 13 \][/tex]
2. Recursive Relationship:
A geometric sequence has a common ratio between consecutive terms. For this sequence, the common ratio [tex]\( r \)[/tex] can be determined from the formula:
[tex]\[ f(n) = 13 \cdot (1.3)^{n-1} \][/tex]
To find the relationship between [tex]\( f(n) \)[/tex] and [tex]\( f(n-1) \)[/tex], consider:
[tex]\[ f(n-1) = 13 \cdot (1.3)^{(n-1)-1} = 13 \cdot (1.3)^{n-2} \][/tex]
To express [tex]\( f(n) \)[/tex] using [tex]\( f(n-1) \)[/tex]:
\begin{align}
f(n) &= 13 \cdot (1.3)^{n-1} \\
&= 13 \cdot (1.3)^{n-2} \cdot (1.3)^1 \\
&= (13 \cdot (1.3)^{n-2}) \cdot 1.3 \\
&= f(n-1) \cdot 1.3
\end{align}
Therefore, the recursive relationship is:
[tex]\[ f(n) = 1.3 \cdot f(n-1) \quad \text{for} \quad n \geq 2 \][/tex]
Combining both the initial term and the recursive relationship, the recursive rule for the geometric sequence is:
[tex]\[ f(1) = 13, \quad f(n) = 1.3 \cdot f(n-1) \quad \text{for} \quad n \geq 2 \][/tex]
Thus, the correct choice is:
\[
f(1)=13, \quad f(n)=1.3 \cdot f(n-1), \quad n\geq 2
\
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.